2021
DOI: 10.5005/jp-journals-10071-23781
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bloodstream Infections and their Etiology in COVID-19 Patients Admitted in a Tertiary Care Hospital in Jaipur

Abstract: A bstract Background World is in grip of coronavirus disease-2019 (COVID-19) pandemic right now. Majority of studies center around its epidemiological and clinical characteristics. Information regarding secondary bacterial infections is limited. This retrospective observational study was done to determine the prevalence and characteristics of bloodstream infections in COVID-19 patients admitted in a tertiary care center in Jaipur. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
3
0
2
Order By: Relevance
“…This study revealed that COVID-19 patients with microbiologically examined infections had E. coli bacteria, consistent with a study finding that 7.0% of COVID-19 patients had secondary bacterial infections caused by E. coli [ 41 ]. According to the current study, E. coli isolates are extremely susceptible to carbapenem antibiotics, including IPM, MEM, and ETP (88, 86, and 92%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that COVID-19 patients with microbiologically examined infections had E. coli bacteria, consistent with a study finding that 7.0% of COVID-19 patients had secondary bacterial infections caused by E. coli [ 41 ]. According to the current study, E. coli isolates are extremely susceptible to carbapenem antibiotics, including IPM, MEM, and ETP (88, 86, and 92%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…We read with interest the article by Rajni et al analyzing the prevalence and etiology of bloodstream infections in coronavirus disease-2019 (COVID-19) patients. 1 The authors concluded that the incidence of bloodstream infections was low in COVID-19 patients. Particularly interesting was the fact that only one case of candidemia occurred in 1,578 patients, a significantly lower rate compared to the incidence of candidemia in other studies.…”
mentioning
confidence: 99%
“…12 Hughes et al (2020) reported a true bacteraemia rate of 3.2% and classified 6.1% as contaminants in a retrospective observational analysis of COVID-19 positive patients across a multicentre NHS acute trust. 15,16 A secondary BSI rate of 8.5% was found in a single-centre retrospective study conducted among SARS-CoV-2 positive patients in an ICU in India. 17 S. aureus, S. pneumoniae and Streptococcus pyogenes are important causes of coinfection or secondary bacterial pneumonia following viral respiratory tract infections.…”
Section: Discussionmentioning
confidence: 97%